Idiomatic Expression in Song Lyrics from Arianna Grande Album Positions - Putri Ristanti; Dyah Nugrahani; Rahmawati Sukmaningrum (International Journal of Research in Education, 2023)
A song is a literary work that can describe a person’s feelings. Many songwriters write the song lyrics according to the feelings they felt at the time. This research aims to (1) classify the types of idiom expressions that were found in song lyrics of the album Positions by Arianna Grande. (2) find out the dominant types of idiom expression found in song lyrics of album Positions by Arianna Grande’s. (3) identify the meaning of idiom expression found in song lyrics of album Positions by Arianna Grande. This research is included in qualitative descriptive research. Researchers have implemented several steps, are a follows: downloading all songs of album Positions from website, searching te scripts lyrics songs, listening to the songs as data for the research been carefully, finding the idiomatic expression in Positions album by Arianna Grande, classifying the idiomatic expression based on the types, finding the idiomatic meanings in Positions album by Arianna Grande. The result of the analysis, the researcher found 16 songs that used the idiomatic expression 22 songs used the types of idiomatic expression phrasal verb. Then, the researcher found 8 songs that used the types of idiomatic expression, preposition verb. In addition, the researcher found 9 songs types of idiomatic expression that used partial idioms. The researcher concluded a percentage: phrasal verb (56.40%), preposition verbs (20.50%), and partial idioms (23.10%). The dominant type of idiomatic expression used in the “Position” album was the phrasal verb type, with the highest percentage of 56.40%.